A história da pétala: etimologia de um termo científico - Maroneze, Bruno (2019)
This study describes the diachrony of pétala (‘petal’), a term of Botany that presents two competing forms in Portuguese: pétala (feminine) and pétalo (masculine). Starting from some theoretical and methodological concepts in Etymology, we initially identified the cognate forms in French, Spanish and Italian; then we sought to find the first dates (the so-called terminus a quo) of the Portuguese forms. We observed that the dates for the Portuguese language are later than those identified for French and Italian, languages in which the same term also presents gender oscillation. Four hypotheses are then considered for the existence of both forms in Portuguese: (1) the feminine as originating from the Latin neuter plural; (2) the influence of the feminine gender of the word folha ‘leaf’; (3) the influence of the adjective apétalo ‘without petals’ in the feminine form; and (4) the influence of the other languages in which there is the same gender oscillation. The conclusion points out that the phenomenon must be explained taking into account the existence of multiple causes, which is a common type of explanation in Etymology.